2015
DOI: 10.1097/md.0000000000001395
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Intake and Neural Tube Defects

Abstract: Neural tube defects (NTDs) are a group of congenital malformations with worldwide distribution and complex etiopathogenesis. Folic acid plays a pivotal role in their prevention. We aimed to identify the protective effect of folic acid intake against NTDs and its dependence on different socioeconomic and environmental factors in a cohort of mothers in Egypt.A cross-sectional study was carried over a period of 12 months on mothers who gave birth to babies with NTDs (group 1) and a control group with healthy offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Six studies [ 18 , 37 – 40 , 51 , 52 ] examined the association between folic acid supplementations before and within the first months of pregnancy. The pooled odds ratio indicated that women who have taken folic acid supplements before pregnancy and within the first month of pregnancy were 60% less likely to have newborns with neural tube defects (POR, 95% CI:0.4 (0.19–0.85)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies [ 18 , 37 – 40 , 51 , 52 ] examined the association between folic acid supplementations before and within the first months of pregnancy. The pooled odds ratio indicated that women who have taken folic acid supplements before pregnancy and within the first month of pregnancy were 60% less likely to have newborns with neural tube defects (POR, 95% CI:0.4 (0.19–0.85)).…”
Section: Resultsmentioning
confidence: 99%
“…The association of paternal consanguineous marriage and neural tube defect was examined based on the findings from six studies [ 17 , 18 , 39 , 52 , 54 , 55 ]. The pooled odds ratio indicated that neural tube defects do not differ among parents with and without consanguineous marriages (POR, 95% CI: 1.42 (.62–3.23)).…”
Section: Resultsmentioning
confidence: 99%
“…ДНТ представляват група тежки вродени аномалии, които са свързани с висока смъртност, неблагоприятна прогноза и дългосрочни увреждания, както и със значителни емоционални, психологически и икономически последствия [4][5]. По данни на СЗО, почти всички (94%) тежки вродени дефекти възникват в слаборазвити страни, най-често поради недохранване на майката при експозиция на тератогенни фактори [6][7].…”
Section: въведениеunclassified
“…Времето за иницииране на прием при 1/3 от страните е най-малко 4 седмици преди зачеване. Въпреки че действащите препоръки се различават между отделните страни, препоръчителният прием на фолиева киселина от 400 µg дневно преди зачеване до първия триместър на бременността е еднакъв за повечето от тях (Таблица 1) [5,13,[24][25][26][27][28][29][30][31]. http://journal.raredis.org Христова Е, Искров Г, Стефанов Р. Преконцепционна употреба на фолиева киселина за първична профилактика на редки генетични заболявания.…”
Section: резултати ролята на фолиевата киселина в общото здравеunclassified